Africology: A Theory of Forces - Van Horne, Winston A. (My University, 2010)
This manuscript is a product of the long years that I have spent in reflection on the discipline of africology. I have written previously of africology as a subject-matter discipline and an institutional discipline. In this essay, I am concerned primarily with africology as an institutional discipline covering five hundred generations of Africans and their planetwide descent, with a special emphasis on the next five generations. In treating africology as an institutional discipline, I, of course, bring its subject matter into play. In structuring the manuscript, I borrow the concept of four natural forces from physics to construct four interlocking social forces?the leadership force, the educational force, the resource force, and the behavioral force?to ground institutional africology. I call out that the behavioral force is the strongest and most complex of the four forces, and indicate ways in which it affects the other three forces and is, in turn, affected by them. I end the essay by hypothesizing about what the state of the planet on which the fifth of the next five generations of Africans and their global progeny will pass their lives. The hypothesis is empirical, not existential, and so it is open to corroboration or confutation in the period of time that has been specified, even though, unhappily, I shall not be around to observe.
Keywords: Africology